Investigation of fatigue failure in composite versus steel coiled tube for application in mine site drilling - Mishani, Siamak (Curtin University, 2017)
Composite coiled tubing could be an economic alternative to the use of steel for exploration drilling due to its potentially greater reliability and higher fatigue life. This PhD study investigated the fatigue life of steel versus composite tubes using both numerical modelling and laboratory scale tests. Results were validated by statistical analysis and confirmed that composite tubing has a higher fatigue life, and potentially opens up a new market place for composite drill pipe.